FKBP5 activates mitophagy by ablating PPAR-γ to shape a benign remyelination environment - Xingzong Sun; Menghan Qian; Hongliang Li; Lei Wang; Yunjie Zhao; Min Yin; Lili Dai; Hongkun Bao (Cell Death and Disease, 2023)
Abstract Multiple sclerosis (MS) is an autoimmune and neurodegenerative disease of the central nervous system (CNS) that is characterized by myelin damage, followed by axonal and ultimately neuronal loss, which has been found to be associated with mitophagy. The etiology and pathology of MS remain elusive. However, the role of FK506 binding protein 5 (FKBP5, also called FKBP51), a newly identified gene associated with MS, in the progression of the disease has not been well defined. Here, we observed that the progress of myelin loss and regeneration in Fkbp5ko mice treated with demyelination for the same amount of time was significantly slower than that in wild-type mice, and that mitophagy plays an important regulatory role in this process. To investigate the mechanism, we discovered that the levels of FKBP5 protein were greatly enhanced in the CNS of cuprizone (CPZ) mice and the myelin-denuded environment stimulates significant activation of the PINK1/Parkin-mediated mitophagy, in which the important regulator, PPAR-γ, is critically regulated by FKBP5. This study reveals the role of FKBP5 in regulating a dynamic pathway of natural restorative regulation of mitophagy through PPAR-γ in pathological demyelinating settings, which may provide potential targets for the treatment of demyelinating diseases.